Targeting cancer stem cells by curcumin and clinical applications - Li, Yanyan; Zhang, Tao (Cancer letters, 2014)
Curcumin is a well-known dietary polyphenol derived from the rhizomes of turmeric, an Indian spice. The anticancer effect of curcumin has been demonstrated in many cell and animal studies, and recent research has shown that curcumin can target cancer stem cells (CSCs). CSCs are proposed to be responsible for initiating and maintaining cancer, and contribute to recurrence and drug resistance. A number of studies have suggested that curcumin has the potential to target CSCs through regulation of CSC self-renewal pathways (Wnt/β-catenin, Notch, sonic hedgehog) and specific microRNAs involved in acquisition of epithelial–mesenchymal transition (EMT). The potential impact of curcumin, alone or in combination with other anticancer agents, on CSCs was evaluated as well. Furthermore, the safety and tolerability of curcumin have been well-established by numerous clinical studies. Importantly, the low bioavailability of curcumin has been dramatically improved through the use of structural analogues or special formulations. More clinical trials are underway to investigate the efficacy of this promising agent in cancer chemoprevention and therapy. In this article, we review the effects of curcumin on CSC self-renewal pathways and specific microRNAs, as well as its safety and efficacy in recent human studies. In conclusion, curcumin could be a very promising adjunct to traditional cancer treatments.